2023
DOI: 10.3389/fnins.2023.1210328
|View full text |Cite
|
Sign up to set email alerts
|

Targeted transcutaneous spinal cord stimulation promotes persistent recovery of upper limb strength and tactile sensation in spinal cord injury: a pilot study

Abstract: Long-term recovery of limb function is a significant unmet need in people with paralysis. Neuromodulation of the spinal cord through epidural stimulation, when paired with intense activity-based training, has shown promising results toward restoring volitional limb control in people with spinal cord injury. Non-invasive neuromodulation of the cervical spinal cord using transcutaneous spinal cord stimulation (tSCS) has shown similar improvements in upper-limb motor control rehabilitation. However, the motor and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…, supporting body weigh in a static standing position, or volitional ankle flex) is lost when the AC stimulation is stopped. 45–47 A similar response was observed for AC lumbar spinal stimulation to facilitate gait in Parkinson's. 62 Therefore, the specific combination of protocol and electrode material defines the outcome of electrostimulation, with DC schemes seeming to favour cell growth and repair.…”
Section: Electrode Materials and Electrostimulation Protocolssupporting
confidence: 57%
See 3 more Smart Citations
“…, supporting body weigh in a static standing position, or volitional ankle flex) is lost when the AC stimulation is stopped. 45–47 A similar response was observed for AC lumbar spinal stimulation to facilitate gait in Parkinson's. 62 Therefore, the specific combination of protocol and electrode material defines the outcome of electrostimulation, with DC schemes seeming to favour cell growth and repair.…”
Section: Electrode Materials and Electrostimulation Protocolssupporting
confidence: 57%
“…This concept has been leveraged to manage symptoms for diverse neurological diseases including Parkinson's, depression, epilepsy, and migraine. 43,44–51 It may also be the basis for other recent applications in which implanted electrode arrays were used to effectively bypass damaged spinal cord regions to overcome functional deficits in clinically functionally complete (total loss of sensory and motor function below the injury) spinal injured patients. 44–47…”
Section: Endogenous Electric Fields and Injury Currents In Animal Tis...mentioning
confidence: 99%
See 2 more Smart Citations
“…Attempts have been made in applying tsES to improve neural transmission across the lesional sites after SCI for motor restoration in the upper limbs ( Inanici et al, 2021 ). For example, previous studies have demonstrated that tsES could immediately modulate the excitability of spinal cord circuits and facilitate voluntary control of the triceps muscle in SCI individuals by using rectangular stimulation waveform with 1 ms bursts of 10 kHz carrier frequency at the level of C5-C6 interspinous space ( Chandrasekaran et al, 2023 ). tsES has also been applied to the spinal cord at the C3-C6 spinal segments to assist in fine motor control of upper limbs, i.e., hand pinch and grip strength, in patients with cervical SCI ( Inanici et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%